2013
DOI: 10.1002/tox.21937
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm biomarker responses on exposure to commercial cypermethrin

Abstract: Cypermethrin is a synthetic pyrethroid insecticide used worldwide in agriculture, home pest control, disease vector control, and food safety. It accumulates in soil. Therefore, traces of cypermethrin may frequently appear in vegetables grown in contaminated soil. There is a push now to develop biomarkers as early warning indicators of environmental pollution. In this study, DNA damage (tail DNA%, tail length, and olive tail moment), the micronucleus, neutral red retention (NRR) time, and pinocytic adherence ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Similarly, Robidoux et al () reported that NRRT was significantly reduced in Eisenia andrei exposed to explosive‐contaminated soils in both field and laboratory studies. Muangphra et al () reported that NRRT was significantly decreased in P. peguana earthworms exposed to cypermethrin in filter paper tests and concluded that NRRT was easier to conduct and a more sensitive indicator of exposure to pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Robidoux et al () reported that NRRT was significantly reduced in Eisenia andrei exposed to explosive‐contaminated soils in both field and laboratory studies. Muangphra et al () reported that NRRT was significantly decreased in P. peguana earthworms exposed to cypermethrin in filter paper tests and concluded that NRRT was easier to conduct and a more sensitive indicator of exposure to pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Insecticides can induce genetic alterations in terrestrial invertebrates. Several studies reported DNA damage in earthworms upon exposure to sublethal concentrations of cypermethrin (Pheretima peguana) [87], the neonicotinoids imidacloprid and dinotefuran (E. fetida) [88,89], and the keto-enol insecticide spirotetramat (E. fetida) [90]. This is not in accordance with Wang et al [91] who found no DNA damage in E. fetida exposed to the neonicotinoid guadipyr at concentrations up to 100 mg a.i.…”
Section: Effect Of Insecticides At Sub-organism Levelmentioning
confidence: 91%
“…Insecticides can affect the structure and integrity of terrestrial invertebrate cells. For instance, cypermethrin negatively affected cell viability in coelomocytes of P. peguana, alongside the micronucleus frequency and pinocytic adherence activity [87]. Leomanni et al [99] documented alterations of hemocyte lysosomal membrane stability in C. apertus as a consequence of carbaryl-induced oxidative stress.…”
Section: Effect Of Insecticides At Sub-organism Levelmentioning
confidence: 99%
“…Coelomic amoebocytes (cells circulating in the coelomic fluid constituting the hydrostatic skeleton of earthworms) are immunocytes involved in a broad range of defence functions (Engelmann et al, 2005;Bilej et al, 2010). However, amoeboid leukocytes, non-invasively extruded from the coelomic cavity, have proved an appropriate target for assessing toxic and genotoxic effects of chemicals, allowing for the detection of sensitive physiological responses in exposed animals (Eyambe et al, 1991;Homa et al, 2005;Sforzini et al, 2012;Hayashi and Engelmann, 2013;Muangphra et al, 2015). Cr(VI) has been found to be involved in the alteration of the immune response in different cell types (Shrivastava et al, 2002;Ciacci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%